The Roles of lncRNA in Myocardial Infarction: Molecular Mechanisms, Diagnosis Biomarkers, and Therapeutic Perspectives - Xie, Luhan; Zhang, Qingqing; Mao, Jun; Zhang, Jun; Li, Lianhong (Frontiers in Cell and Developmental Biology, 2021)
In recent years, long non-coding RNAs(lncRNAs) have been demonstrated to be associated with many physiological and pathological processes in cardiac. Recent studies have shown that lncRNAs are expressed dynamically in cardiovascular diseases and participate in regulation through a variety of molecular mechanisms, which have become a critical part of the epigenetic and transcriptional regulatory pathways in heart development, as well as the initiation and progress of myocardial infarction. In this review, we summarized some current research about the roles of lncRNAs in heart development and myocardial infarction, with the emphasis on molecular mechanisms of pathological responses, and highlighted their functions in the secondary changes of myocardial infarction. We also discussed the possibility of lncRNAs as novel diagnostic biomarkers and potential therapeutic targets for myocardial infarction.